2018
DOI: 10.1111/1471-0528.15216
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine adhesions following an induced termination of pregnancy: a nationwide cohort study

Abstract: IUA is rare after induced termination of pregnancy (iTOP), but surgical evacuation is a risk factor for IUAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…A nationwide study from Finland evaluated 79 960 women who had induced termination of pregnancy and depending on the diagnostic codes of medical records, they reported a rate of 1.5 and 2.0 cases per 10 000 medically and surgically induced terminations of pregnancies, respectively 13 . A study evaluating the risk factors of Asherman Syndrome among 61 patients reported induced abortions and miscarriages were the main risk factor for IUA 14 …”
Section: Discussionmentioning
confidence: 99%
“…A nationwide study from Finland evaluated 79 960 women who had induced termination of pregnancy and depending on the diagnostic codes of medical records, they reported a rate of 1.5 and 2.0 cases per 10 000 medically and surgically induced terminations of pregnancies, respectively 13 . A study evaluating the risk factors of Asherman Syndrome among 61 patients reported induced abortions and miscarriages were the main risk factor for IUA 14 …”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine adhesion (IUA), also referred to as Asherman syndrome, is a complication of partial or full adhesion in the uterine cavity due to fibrous tissue proliferation after uterine wall and endometrial injury during pregnancy (1,2). IUA can not only cause menstrual disorders including oligomenorrhea, amenorrhea and periodic lower abdominal pain, but also fertility disorders such as infertility, abortion, and placental abnormalities (3).…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine adhesion (IUA) is characterized by reduced menstrual blood volume, amenorrhea, infertility, and recurrent abortion (1), which seriously affects the reproductive health of women. Hysteroscopy is the preferred diagnostic method for IUAs; transcervical resection of adhesion (TCRA) is the standard surgical procedure to treat IUAs and plays an irreplaceable role in separating IUAs (2).…”
Section: ' Introductionmentioning
confidence: 99%